Metabolic Syndrome in First Episode Schizophrenia, Based on the National Mental Health Registry of Schizophrenia (NMHR) in a General Hospital in Malaysia: A 10-Year Retrospective Cohort Study - Lee, Albert Muh Haur; Ng, Chong Guan; Koh, Ong Hui; Gill, Jesjeet Singh; Aziz, Salina Abdul (MDPI, 2018)
Schizophrenia has been linked with various medical comorbidities, particularly metabolic syndrome. The number of studies on this aspect is lacking in Malaysia. (1) Objective: To investigate metabolic syndrome rates and its associated factors. (2) Method: This is the first 10-year retrospective-outcome study of patients with first episode schizophrenia in Malaysia. Out of 394 patients diagnosed with first episode schizophrenia and registered with the National Mental Health Registry of Schizophrenia (NMHR) in the General Hospital Kuala Lumpur (GHKL) in 2004–2005, 174 patients consented to participate in the study. They were interviewed using a Schizophrenia outcome questionnaire and the International Physical Activity Questionnaire (IPAQ). The diagnosis of metabolic syndrome was made using the National Cholesterol Education Program—Third Adult Treatment Panel (NCEP ATP III). (3) Results: All patients’ weight, body mass index, fasting blood sugar, and blood pressure are significantly increased. Sixty-three subjects (36.2%) developed metabolic syndrome while 36 (23.2%) were hypertensive, and 41 (28.1%) were diabetic. Use of fluphenthixol depot (CI = 1.05–5.09, OR: 0.84, p = 0.039), reduced physical activity (CI = 0.13–1.00, OR: −1.04, p = 0.049), and substance use disorder (CI = 1.40, 13.89, OR: 1.48, p = 0.012) were significantly associated with metabolic syndrome based on univariate analysis. In further multivariate analysis, comorbid substance abuse was the only significant factor associated with metabolic syndrome after adjusting for physical activity and intramuscular depot. (4) Conclusion: Patients with schizophrenia are at high risk of metabolic syndrome. It is important to address substance use problems as an important risk factor of this comorbidity.